The Light of Zen in the West : incorporating the supreme doctrine and the realizationof the self (Sussex Academic Press, 2020)
This Centenary Commemorative Edition also includes two lesser known works Buddha and the Intuition of the Universal and Techniques of Timeless Realization. The volume is complemented by a detailed Glossary, an Index, an Original Foreword by Aldous Huxley (1955), an Original Preface by Swami Siddheswarananda (1955), and a Contemporary Foreword by Professor Asanga Tilakaratne. Benoits writings on the human predicament and the path to inner freedom were influenced by his studies in Zen Buddhism and psychoanalysis. There is, as well, an evident dialogue in Benoits writings between the Gurdjieff teaching and Zen, with insightful ideas about universal laws, inner work, the human machine, and work in life. The Supreme Doctrine and The Realization of the Self foreshadow contemporary transpersonal and integral psychology: through the re-integration of psychology and metaphysics, Benoit invites us to make our own journey toward spiritual transformation and the intuitive understanding of universal truths. This Centenary Commemorative Edition also includes two lesser known works Buddha and the Intuition of the Universal and Techniques of Timeless Realization. The volume is complemented by a detailed Glossary, an Index, an Original Foreword by Aldous Huxley (1955), an Original Preface by Swami Siddheswarananda (1955), and a Contemporary Foreword by Professor Asanga Tilakaratne.